Enhanced ZEB 1 stromal expression is a marker for epithelial mesenchymal transition in oral submucous fibrosis - Gouri S. Panchannavar; Punnya V. Angadi (Elsevier, 2024)
Introduction: Oral submucous fibrosis is a progressive oral mucosal condition that is characterized by inflammation and persistent fibrosis. Epithelial Mesenchymal Transition is a crucial molecular event that contributes to tumor progression and fibrosis, with ZEB 1 and its effect on E-cadherin expression being key molecules in the process. Thera are no tissue level studies of these molecules in oral submucous fibrosis. Objective: To evaluate the immunohistochemical expression of epithelial mesenchymal transition markers E-cadherin and ZEB1 in oral submucous fibrosis. Methodology: A total of 30 cases of Oral submucous fibrosis (15 Early OSMF and 15 Advanced OSMF) classified based on the histopathological features were included in the study. Immunohistochemistry was done using two markers i.e. E-cadherin and ZEB1. The difference in the expression of E-Cadherin and ZEB1 among histo-pathological grades of OSMF was done by Mann-Whitney U test. Results: A slight reduction in the E-cadherin expression was noted in Oral submucous fibrosis but marked enhanced expression of ZEB1 was seen in the connective tissue of OSMF. Conclusion: An increase in intensity and percentage of positivity of ZEB 1 expression in connective tissue was observed in advanced cases as compared to early OSMF. This can be attributed to role of ZEB1 in mediating EMT via transdifferentiation of fibroblast into myofibroblast and thus predispose to fibrosis in OSMF.